(untitled) (VETERINARIA, 2020)
During the last several decades radiation therapy of superficial tumors by megavoltage electron beams has been widely applied in human and veterinary medicine. The objective of our research was to investigate clinical and pathohistological changes in the rabbit skin during a 90-day period after a single local electron beam irradiation of posterior extremity, and to investigate the impact of the single application dose of irradiation on dynamics and severity of acute skin changes in rabbits. Experimental trial was conducted on 18 adult New Zealand white rabbit males divided into 3 groups of 6 rabbits, whose left posterior extremity was irradiated with a single total dose of 55, 65 and 75 Gy, respectively, on the field size 10x10 cm, using 6 MeV beams. Clinical observation of the skin changes during the 90-day postradiation period in all the three experimental groups of rabbits singly irradiated by megavoltage electron beams in total doses of 55, 65 i 75 Gy resulted in occurrence of epilation, erythema, dryndesquamation, edema, moist desquamation, secondary ulceration, and reparation. Severity of the main acute responses of the rabbit skin such as erythema, and dry and moist desquamation was proportional to the single high dose of megavoltage electron irradiation, and was reflected in time between irradiation to clinical symptoms as well as the duration of symptoms. Pathohistological changes in the rabbit skin and subcutaneous tissue were observed on the 20th, 50th, and 90th day upon irradiation, and their severity was growing in proportion with the dose (55, 65 i 75 Gy) following the dynamics and severity of the acute clinical skin changes.